Origins and diameter of the anterior choroidal artery - (:unkn) unknown (My University, 2009)
Objective: The anterior choroidal artery(AChoA) may be involved in cases of intracranial aneurysms, arteriovenous malformations (AVMs) or intracranial tumors. The diagnostic evaluation of the anterior choroidal artery is required in order to obtain knowledge of the anatomy of this vessel, therefore we decided to examine their origin and diameters in detail. Methods: Eighty cerebral hemispheres from 40 autopsy cases (11 female, 29 male) aged between 20 and 71 years were obtained as soon as possible after death. Forty μ m thickness of transverse sections were cut by cryostat. The average diameter was calculated. Sex and side differences were statistically analyzed. Results: AChoA were present in 75 (93.75%) hemispheres, whereas in 5 cerebral hemispheres (6.25%) the AChoA was absent. In all autopsy cases, it arose from the posterior wall of the internal carotid artery (ICA) (100%). The inner diameter of the AChoA was 0.56±0.15mm in females;0.58±0.18mm in males. The outer diameter of the AChoA was 0.67±0.17mm in females;0.70±0.16mm in males. No statistically significant difference between genders in terms of the inner and outer diameters of AChoA were found. Conclusion: For the endovascular treatment of AChoA aneurysms, the knowledge of the inner diameter gains importance.
Keywords: Artery; Choroidal; Diameter; Origin